2016
DOI: 10.21037/jss.2016.11.02
|View full text |Cite
|
Sign up to set email alerts
|

Anterior to psoas (ATP) fusion of the lumbar spine: evolution of a technique facilitated by changes in equipment

Abstract: Background: Lateral interbody cages have been proven useful in spinal fusions. Spanning both lateral cortical rims while sparing the Anterior Longitudinal Ligament, the lateral interbody cages restore and maintain disc height while adding stability prior to supplemental fixation. The standard approach for their insertion is by a 90-degree lateral transpsoas method. This is relatively bloodless compared to other techniques although has its limitations, requiring neuro-monitoring and being, at times, very diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…No significant association was found between corridor sizes with gender. Indeed, these morphometric studies are in keeping with the clinical experience by initial ATP/OLIF studies (2,6,11), where a left sided approach is preferable to all but L5/S1 disc space, as a right sided approach is more likely to require mobilization of the inferior vena cava. At L5/S1 a right sided approach may be preferred as the right common iliac vein is typically more lateral and unlike the left, rarely adherent to the spine or disc space.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…No significant association was found between corridor sizes with gender. Indeed, these morphometric studies are in keeping with the clinical experience by initial ATP/OLIF studies (2,6,11), where a left sided approach is preferable to all but L5/S1 disc space, as a right sided approach is more likely to require mobilization of the inferior vena cava. At L5/S1 a right sided approach may be preferred as the right common iliac vein is typically more lateral and unlike the left, rarely adherent to the spine or disc space.…”
Section: Discussionsupporting
confidence: 71%
“…However, the standard lateral approach, which traverses the psoas muscle (i.e., transpsoas approach), has its own limitations and complications (2)(3)(4)(5)(6). Of most concern is the potential for injury to the lumbar plexus, minimized by using intraoperative neuromonitoring (7).…”
Section: Introductionmentioning
confidence: 99%
“…In the current reports, the incidences of sympathetic chain injury were varied, ranging from 1.7% to 8.7%. Between the anterior longitudinal ligament as a medial landmark and the psoas muscle as a lateral landmark is the natural “safety” corridor, which is covered by the fibers of the sympathetic chain.…”
Section: Development Of Oblique Lumbar Interbody Fusionmentioning
confidence: 88%
“…Javier suggests a tubular stretcher being placed behind the sympathetic chain to decrease the incidence of traction lesions. Gragnaniello demonstrated that the sympathetic trunk has to be mobilized by smooth retractor blades; even sacrifice produces only warming of the affected leg that is unnoticed by patients.…”
Section: Development Of Oblique Lumbar Interbody Fusionmentioning
confidence: 99%
“…Using a lateral approach, interbody cage placement can be conducted either from the front of the psoas muscle (oblique lumbar interbody fusion, OLIF) or through the psoas muscle (direct lateral interbody fusion, DLIF) [8,9]. Both techniques facilitate the insertion of a wide-bodied interbody cage via a minimally invasive approach.…”
Section: Introductionmentioning
confidence: 99%